Distinct effects of semaglutide and tirzepatide on metabolic and inflammatory gene expression in brown adipose tissue of mice fed a high-fat, high-fructose diet - Ma, Tianyi; Song, Fanfan; Pan, Yongning; He, Ying; Cao, Xinming; Zhang, Yan; Song, Guangyao; Ren, Luping (Frontiers in Nutrition, 2025)
BackgroundBrown adipose tissue (BAT) is crucial for overall energy homeostasis as a thermogenic organ with high metabolic activity. While the recruitment of BAT contributes to improved glycemic and lipid homeostasis, the exact molecular mechanisms remain incompletely understood.ObjectiveThis investigation compared the transcriptomic responses of semaglutide (GLP-1 receptor agonist) and tirzepatide (dual GIP/GLP-1 receptor agonist) on BAT in mice fed a high-fat, high-fructose diet (HFHFD). These outcomes enhance our understanding of the metabolic actions of GLP-1 and dual GIP/GLP-1 receptor agonists, providing a conceptual basis for future BAT-targeted therapeutic strategies.MethodsTwenty-eight male C57BL/6J mice were randomly assigned to either a control group (CON; n = 7, standard diet) or an obesity model group (n = 21, HFHFD). Following the establishment of obesity, the obese mice were further randomized into three intervention groups (n = 7) and administered subcutaneous injections of saline, semaglutide, or tirzepatide for 7 weeks. Metabolic parameters (including body weight, glycemic and lipid profiles, and insulin levels) and BAT morphology were assessed. RNA sequencing of BAT was conducted to identify differentially expressed genes (DEGs), followed by gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein–protein interaction (PPI) analyses. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was subsequently employed to validate the expression of selected DEGs.ResultsBoth semaglutide and tirzepatide reduced body weight, improved lipid profiles, and enhanced insulin sensitivity. Compared with the saline group, administration of semaglutide led to differential expression of 467 genes (199 downregulated and 268 upregulated), whereas tirzepatide modulated 40 genes (20 downregulated and 20 upregulated). Bioinformatic analysis identified Cyp1a1, Hsd11b1, Atp1a3, Tfrc, Ptger4, and Il1b as potential therapeutic targets.ConclusionSemaglutide and tirzepatide may share common targets (Cyp1a1, Hsd11b1, and Atp1a3) that enhance insulin sensitivity, improve metabolism, and promote weight loss. Tfrc, Ptger4, and Il1b may also serve as tirzepatide-specific targets, potentially elucidating its enhanced anti-inflammatory and metabolic regulatory effects.